Newcastle disease vaccination regimen comprising both Lentogenic and Mesogenic strains is more effective than Lentogenic strain only (Bangladesh Veterinarian, 2010)
Two vaccination regimens against Newcastle disease were compared. A total of 180crossbred (RIR × Fayoumi) day-old chicks were obtained from the government PoultryFarm. At three days of age, 10 birds were randomly selected and killed to obtain bloodsamples for serum collection. The remaining 170 birds were divided into three groups.Group A, (55) received a locally produced live lentogenic Newcastle disease virus (NDV)vaccine called “Baby Chick Ranikhet Disease Vaccine” (BCRDV) intraocularly at threeand 28 days of age followed by a live mesogenic NDV vaccine namely “Ranikhet DiseaseVaccine” (RDV) intramuscularly at 60 days of age. Group B, (55) was vaccinated with animported live lentogenic commercial vaccine intraocularly at three, 28 and 60 days of age.Group C, (60) served as unvaccinated control. Further blood samples were collected onday 28, 60 and 74 from all groups. All the sera were tested for haemagglutinationinhibition (HI) antibody titre to NDV. At 75 days of age, 30 birds from each of the twovaccinated groups and 32 birds from the unvaccinated group were challenged with avelogenic viscerotropic field isolate of NDV. The chicks had a high level of maternal HIantibodies at three days of age with a geometric mean titre (GMT) of log2 4.8, but thatgradually declined in the unvaccinated group. Following vaccination there was noremarkable rise in the antibody titre at 28 and 60 days of age (GMT>log2 3.5), but at 74days of age, the GMT of HI antibody in Group A (log2 5.9) was significantly higher thanthat in the Group B (log2 4.1). Following challenge, 100% morbidity and 65.6% mortalitywere observed in the unvaccinated group. Among the vaccinated groups, only 16.7%morbidity and no mortality were noticed in Group A but 43.3% morbidity and 10%mortality were observed in Group B. It is suggested that a vaccination programme basedon lentogenic priming and mesogenic booster gave better protection against velogenicviscerotropic NDV challenge than that based on lentogenic vaccine only. (Bangl. vet. 2010. Vol. 27, No. 1, 1 – 7)DOI: 10.3329/bvet.v27i1.5908